A Rare Clinical Course of Seronegative Pulmonary-Renal Syndrome. (27th October 2016) - Fröhlich-Gildhoff, M.; Jabs, W. J.; Berhold, C.; Kuhlmann, M. K.; Ketterer, U.; Kische, S.; Ince, H.
Abstract : Purpose . Pulmonary-renal syndrome (PRS) is characterized by diffuse alveolar hemorrhage and rapidly progressive glomerulonephritis mainly due to autoimmune etiologies. Seronegative PRS is a challenging entity to the clinician, since early diagnosis may be missed leading to delayed appropriate treatment. Materials and Methods . We present the clinical course of a 77-year-old patient who was admitted under the suspected diagnosis of pneumogenic sepsis and septic renal failure with fever, dyspnea, and elevated CRP levels. The diagnosis of pulmonary-renal syndrome was initially missed because of the absence of autoantibodies in all serological findings. Results. Despite delayed initiation of immunosuppressive therapy and a prolonged period of dialysis and extracorporeal membrane oxygenation the patient recovered well and was released to a rehabilitation center with nearly normalized creatinine levels. The diagnosis of PRS was established by renal biopsy. Conclusion . This case illustrates the important differential diagnosis of seronegative pulmonary-renal syndrome in patients with pulmonary and renal impairment.